STRATEGI PEMASARAN PADA USAHA BAKSO MAS PUR DI SATRIAJAYA-KABUPATEN BEKASI - Kurniawan, M. Taufik; Rahmanto, Muhammad Ikhwan; Ardisela, Dawud (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2024)
The study bakso mas pur warung business is a well-known culinary business in bekasi regency, which is located at jl. Pisangan, kebon cassava, rt.01/rw.001 satriajaya village, tambun utara district, bekasi regency, this study aims to identify internal factors (strengths and weaknesses), and external factors (opportunities and threats) as well as to determine the marketing strategy. The method used in this study is a case study with a descriptive approach and data analysis consisting of an ife matrix, an efe matrix, an ie matrix and a swot matrix. The results of this research on the warung bakso mas pur business are in cell i position. The position of using the strategy that should be applied by the warung bakso mas pur business is grow and build or a strategy of growing and building. This strategy is in line with the so strategy of creating product variations at competitive prices, the wo strategy of optimizing the internet as a promotional medium and online marketing to expand marketing reach, and the wt strategy of maintaining a good name and maintaining prices to face competition well.